Enhanced sodium-ion storage capability of P2/O3 biphase by Li-ion substitution into P2-type Na0.5Fe0.5Mn0.5O2 layered cathode. (10th February 2019) - Veerasubramani, Ganesh Kumar; Subramanian, Yuvaraj; Park, Myung-Soo; Senthilkumar, Baskar; Eftekhari, Ali; Kim, Sang Jae; Kim, Dong-Won
Abstract: Integration of P2 and O3 phases in Na0.5 Fe0.5 Mn0.5 O2 cathode via Li-ion substitution is proposed to enhance its electrochemical performance for sodium-ion battery applications. The formation of P2 and the combination of P2/O3 intergrowth were confirmed by X-ray diffraction refinement, high resolution transmission electron microscopy and X-ray photoelectron microscopy analyses. Various content of lithium was used to find optimum P2+O3 combinations. The optimized Li-ion substituted Na0.5 (Li0.10 Fe0.45 Mn0.45 )O2 showed a high initial discharge capacity of 146.2 mAh g −1 with improved cycling stability, whereas the pristine Na0.5 Fe0.5 Mn0.5 O2 initially delivered a discharge capacity of 127.0 mAh g −1 . In addition, the combination of P2+O3 increased its average voltage, which is important for achieving high energy density sodium-ion batteries. Overall, the prepared Na0.5 (Li0.10 Fe0.45 Mn0.45 )O2 electrode exhibited the improved cycling performance in terms of reversible capacity and rate capability compared to pristine Na0.5 Fe0.5 Mn0.5 O2 electrode material. Graphical abstract: Image 1 Highlights: Facile sol-gel route is used to synthesis of layered cathode via Li-ion substitution. Combination of P2 and O3 phases is confirmed using XRD refinement results. P2+O3 Na0.5 [Li0.10 Fe0.45 Mn0.45 ]O2 biphasic cathode exhibits good cycling performance.